Working of Welfare Hostels in Dadra and Nagar Haveli - Planning Commission (Planning Commission, 1982)
Welfare Hostel Schemes of the Government of India aims at improving the socio-economic conditions of the scheduled tribes, scheduled castes and economically backward communities living in tribal concentration areas of the country by promoting literacy and education amongst them . The Government of India provides financial assistance in the form of grant-in-aid to run the welfare host-ls in the union territory of Dadra and Nagar Haveli. the ministration of Dadra and Nagar Haveli, wherein scheduled tribes accounted for about 87 per of the total population in 1947, launched the first welfare Hostel Scheme in 1961 at Silvassa.
Programme Evaluation Organisation Planning Commission Government of India